(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The economic rate of nutrients was determined with eight different fertilizer treatment applied on T. aman rice (var. Binadhan-7) in Old Brahmaputra Floodplain Soils (AEZ-9) during 2012 and 2013 at Trisal, Mymensingh. The experiment was laid out in a randomized complete block design (RCBD) with three replications. The treatment combinations were: T1 (N64 P14 K28 S6 Zn1), T2 (N80 P14 K28 S6 Zn1), T3 (N80 P17.5 K28 S6 Zn1), T4 (N80 P14 K35 S6 Zn1), T5 (N64 P17.5 K35 S6 Zn1), T6 (N80 P17.5 K35 S6 Zn1), T7 (N48 P10.5 K21 S4.5 Zn0.75), and T8 (control). Grain and straw yields were significantly affected by the application of fertilizers at different rates. Results revealed that the average highest grain (4.86 t ha-1) was recorded in T6 (N80 P17.5 K35 S6 Zn1) treatment and straw yield (5.34 t ha-1) was recorded in treatment T3 (N80 P17.5 K28 S6 Zn1) which is 132.54% and 86.06% respectively higher over control treatment. The second highest grain yield (4.77 t ha-1) was obtained in T3 treatment and straw (5.18 t ha-1) was recorded in T6 treatment. Average (2012 & 2013) nutrient uptake (grain and straw) was the highest in T3 treatment. Partial budget analysis demonstrated the highest net benefit of Tk. 69,673 ha-1 in T6 followed by Tk. 68,833 ha-1 in T3 and the highest MBCR (4.29) was obtained in T3 treatment. The present investigation suggests that treatment T3 (N80 P18 K28 S6 Zn1) might be the best profitable fertilizers dose to sustain Binadhan-7 rice production in Old Brahmaputra Floodplain Soils. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22096 J. Environ. Sci. & Natural Resources, 6(2): 55-59 2013